Book Review of "Right of Boom: The Aftermath of Nuclear Terrorism" by Benjamin E. Schwartz - Kyle Mangrum (International Journal of Nuclear Security, 2017)
Right of Boom: The Aftermath of Nuclear Terrorism is Benjamin Schwartz’s first book. An ex-U.S.-government official, Schwartz presents a hypothetical scenario in which an unknown terrorist organization uses an Improvised Nuclear Device to attack Washington D.C. The book explores the possible consequences of such an attack on U.S. domestic and foreign policy, as well as upon the rest of the world. Schwartz projects outcomes by considering how past interactions and crises involving nuclear weapons have been handled. Thus, the book serves as a history of nuclear security interspersed with extrapolations into the future of nuclear terrorism, based on historical precedents related to nuclear weapons and terrorism.